TINJAUAN YURIDIS EKSPLOITASI ABK INDONESIA DALAM TINDAK PIDANA PERDAGANGAN ORANG - umi kurniawati (Fakultas Hukum Universitas Islam Malang, 2021)
ABSTRACT Human trafficking is a basic form of exploitation of slavery or slavery-like practices. The forms of exploitation that are carried out in trafficking in persons, whether individuals, organized groups or corporations. Currently, the laws and regulations in Indonesia regulate the eradication of the criminal act of trafficking in persons and its punishment. However, there are still articles which in this regulation do not deter victims. perpetrators of the exploitation of Indonesian crew members in trafficking in persons participate in or participate in other acts in it, where these other acts also violate statutory regulations, then they will be subject to criminal sanctions.Keywords : Human Trafficking, Exploitation, Legal Protection. ABSTRAKPerdagangan Orang merupakan suatu bentuk pokok dari adanya eksploitasi perbudakan atau praktik serupa perbudakan. Bentuk-bentuk eksploitasi yang dilakukan dalam perdagangan orang baik itu perorangan, kelompok terorganisir maupun korporasi. Perundang-undangan di Indonesia saat ini telah mengatur peraturan mengenai pemberantasan tindak pidana perdagangan orang serta pemidanaannya. Namun masih saja ada pasal yang dalam peraturan tersebut justru tidak membuat korban menjadi jera. pelaku eksploitasi ABK Indonesia dalam perdagangan orang turut serta atau penyertaan dalam perbuatan lain didalamnya, dimana perbuatan lainnya tersebut juga melanggar peraturan perundang-undangan maka akan dikenakan sanksi pidana.Kata Kunci : Perdagangan Orang, Eksploitasi, Perlindungan Hukum.